Effect of Discharge plan on Patient's Outcomes Undergoing Trans-Hepatic Arterial Chemoembolization (Journal of Pharmaceutical Negative Results, 2023)
Background: Hepatocellular carcinoma (HCC) is the most common primary liver cancer, with more than 1 million deaths expected worldwide in 2030. Transhepatic arterial chemoembolization (TACE) is one of the most commonly used non-surgical therapeutic methods for HCC. Prompt discharge nursing planning is aimed to expand knowledge concerning TACE, promote self-care practices, improve clinical outcomes and minimize readmission. The aim of this study was to evaluate the effect of discharge plan on patient's outcomes TACE. Research design: A quasi experimental research design was used. Setting: The study was conducted in interventional radiology center and arterial catheterization at surgical Zagazig University Hospitals. The study sample composed of seventy adult patients, purposeful selected from both sexes. Tools: Four tools were utilized for data collection, pertinent as follow: Self-administered questionnaire, self-reported practice, assessment quality of life by using Functional Assessment of Cancer Therapy-Hepatobiliary (FACT-Hep) version 4 and Patient's Outcomes Assessment Complications Questionnaire. Results: revealed that, majority of the studied patients were male, 41.4% aged from 50-60 years and 38.3% of studied patients made TACE before. There were statistically significant improvements in patients’ knowledge, practice, therapeutic effect, quality of life and good outcome. Conclusion: the discharge plan had positive effect on improving patient’s outcomes undergoing TACE through the enhancement of their knowledge and practices. Recommendations: Regular follow-up for all patients with HCC undergoing TACE to evaluate their health conditions, detect the complications early and improve their quality of life.